Adjustment to agricultural policy reform: Issues and lessons from the New Zealand experience - Allan Rae; Chris Nixon; Ralph Lattimore (New Zealand Institute of Economic Research (NZIER), 2004)
Pressures for the reform of agricultural policies in wealthy countries will increase. Current policies are expensive and inefficient and impose substantial costs on countries that cannot afford to subsidize their agricultural sectors. A major political impediment to policy reform is the real or assumed costs of adjustment that would be imposed on farmers. In this paper, we illustrate some of the key issues by reference to the New Zealand experience. Issues covered include adjustments in output and input markets, productivity and innovation. Adjustments by farmers and others, along with reforms outside of agriculture, ensured that farm incomes and the agricultural sector recovered from the initial shock of deregulation.
Keywords: 330; Agrarpolitik; Agrarreform; Neuseeland